Perbedaan Ketersediaan Alat Pembawa Vaksin di Pulau Jawa dan Papua: Analisis Komparatif Dua Kelompok Sampel - Mohamad Anis Fahmi (Ficco Public Health Journal, 2024)
Background: One of the important functions of a vaccine carrier is to ensure that the vaccine is still fit for use. The vast area in Indonesia makes development still uneven between areas near and far from the capital. Java is the center of government, while Papua is one of the islands farthest from Java. The purpose of this study was to analyze the differences in the availability of vaccine carriers in Java and Papua. Methods: This is an analytic observational study with secondary data from the Risfaskes reports in 2011 and 2019. The subjects were all districts/cities in Java and Papua. The variabels measured were the availability of vaccine carriers in 2011 and 2019, and the availability of cold boxes, vaccine carriers, and flasks in 2019. Mann Whitney was used for unpaired data. A paired T-test and Wilcoxon were used to analyze differences for two groups of paired data. Data normality tests were performed with descriptive (histogram) and analytical methods. Analytical methods using Kolmogorov Smirnov for Java (n> 50) and Shapiro Wilk for Papua (n ≤50). Results: The average availability of vaccine carriers in Papua was lower than in Java. There was a significant difference between Java and Papua, both in 2011 and 2019. There were also significant differences in the availability of vaccine carriers between 2011 and 2019 in the two islands. Conclusions: It is necessary to increase the equitabel distribution of health development, especially vaccine carriers outside Java to achieve a high degree of health evenly throughout Indonesia.